2007
DOI: 10.1007/s00383-007-1949-z
|View full text |Cite
|
Sign up to set email alerts
|

Large adrenal ganglioneuroma with left inferior vena cava: implications for surgery

Abstract: The contemporaneous occurrence of adrenal ganglioneuroma and left-sided inferior vena cava is uncommon and is previously never reported. We present a case wherein the two entities were fortuitously associated on preoperative imaging. This information facilitated successful surgical resection and avoided catastrophic vascular injury. A review of literature of the common venous anomaly affecting therapeutic decision-making is also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The left suprarenal and gonadal veins are often direct tributaries of the left-sided IVC [although the left gonadal vein may drain into the left renal vein as normal (Castillo et al, 2008)]. The right suprarenal and gonadal veins frequently drain into the right renal vein (Forster et al, 2006;Qureshi et al, 2008;Ekwenna et al, 2011). The common iliac veins usually join posterior and to the left of the aortic bifurcation.…”
Section: Discussionmentioning
confidence: 99%
“…The left suprarenal and gonadal veins are often direct tributaries of the left-sided IVC [although the left gonadal vein may drain into the left renal vein as normal (Castillo et al, 2008)]. The right suprarenal and gonadal veins frequently drain into the right renal vein (Forster et al, 2006;Qureshi et al, 2008;Ekwenna et al, 2011). The common iliac veins usually join posterior and to the left of the aortic bifurcation.…”
Section: Discussionmentioning
confidence: 99%
“…Typical symptoms of PHEO and PGL including the noticeable triad of palpitations, headaches, and sweating, nevertheless, cases of asymptomatic PHEO and PGL are increasing owing to the prevalence of physical examination, family and germline mutation testing (1,2). Unlike cases of PHEO with inferior vena cava (IVC) tumor thrombus that had been sporadically reported (3)(4)(5), PGL with IVC tumor thrombus is even rarer and only two cases Case Report Functional paraganglioma with tumor thrombus in the inferior vena cava, first case report had been publicly reported before, both of them were subclinical, asymptomatic, and accidentally discovered (6,7), report of PGL with the neuroendocrine function that invades the IVC is lacking. We present the following article in accordance with the CARE reporting checklist (available at http://dx.doi.org/10.21037/tau-21-50).…”
Section: Introductionmentioning
confidence: 99%
“…These principles enable good tumour clearance while minimising the morbidity of surgery. Variations in vascular anatomy may be unexpected and challenging.Previous case studies have reported the association of IVC anomalies with Wilms' tumour(2) and ganglioneuroma(3) in children. However, this is the first case report of an abdominal neuroblastoma found in a child with a left IVC anomaly.…”
mentioning
confidence: 99%